Evaluation of the levels of pain when leukocyte and platelets-rich fibrin (PRF) applied inside the alveoler socket on the retraction of upper canines - العمر عبد القادر; حسن حازم (Latakia University Journal -Medical Sciences Series, 2022)
This randomized controlled clinical trial aims to evaluate the effect of platelet-rich fibrin on associated pain during its application after extraction of the upper first premolar and to assess the patient’s acceptance of the procedure. Research materials and methods: a randomized controlled clinical study, split mouth technique was used platelet-rich fibrin was applied on one side immediately after extraction, and on the second side orthodontic movement was done without applying platelet-rich fibrin, as the sample included 10 patients (6 females and 4 males) a questionnaire based on a set of questions was answered by patients given after 1 day 3 days 7 days using the VAS metrics, the T.TEST test was used at a confidence interval of 95%. Results: There is a statistically significant difference between the control group and study group for the studied variable (pain) one day after the platelet-rich fibrin application within the socket in the course of orthodontic treatment and on the third day as well, where the probability value is (0.0052-0.0066), respectively. While the difference between the two sides was not significant on the seventh day after applying fibrin compared with the control side, where the probability value was greater than 0.05 at the 95% confidence level. Conclusions: It was observed that the application of platelet-rich fibrin within the socket after extraction when the upper canines were moved, led to a significant decrease in pain values.